Estratégias para promover a generalização: revisões de escopo em pesquisas aplicadas à população com TEA - Meletti, Helena Duran (2024)
Individuals with Autism Spectrum Disorder (ASD) often face difficulties in generalizing and maintaining learned behaviors across different contexts. This dissertation investigates strategies to promote the generalization of behaviors in individuals with ASD, based on the frameworks proposed by Stokes and Baer (1977), Cooper et al. (1987/2020), and Stokes and Osnes (1989), which suggest a pragmatic approach to the definition of generalization. Through two scoping reviews, categories of strategies to program generalization were explored, both across a broad range of target behaviors and specifically in studies aimed at increasing behavioral variability. The results indicate that generalization strategies have been widely employed in research, particularly those involving the arrangement of antecedent stimuli. However, a more in-depth analysis revealed that successful generalization depends on teaching-related variables which, when carefully planned, facilitate generalization through the establishment of stimulus control during training rather than through the deliberate implementation of the strategies themselves in the studies